Association between Probiotics and Modulation of Gut Microbial Community Composition in Colorectal Cancer Animal Models: A Systematic Review (2010–2021) - Shabnam Zeighamy Alamdary; Shahnaz Halimi; Akram Rezaei; Roghayeh Afifirad (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Colorectal cancer (CRC) is one of the most prevalent gastrointestinal malignancies and is considered the third major cause of mortality globally. Probiotics have been shown to protect against the CRC cascade in numerous studies. Aims. The goal of this systematic review was to gather the preclinical studies that examined the impact of probiotics on the alteration of gut microbiota profiles (bacterial communities) and their link to colorectal carcinogenesis as well as the potential processes involved. Methods. The search was performed using Scopus, Web of Science, and PubMed databases. Five parameters were used to develop search filters: “probiotics,” “prebiotics,” “synbiotics,” “colorectal cancer,” and “animal model.” Results. Of the 399 full texts that were screened, 33 original articles met the inclusion criteria. According to the current findings, probiotics/synbiotics could significantly attenuate aberrant crypt foci (ACF) formation, restore beneficial bacteria in the microbiota population, increase short-chain fatty acids (SCFAs), and change inflammatory marker expression. Conclusions. The present systematic review results indicate that probiotics could modulate the gut microbial composition and immune regulation to combat/inhibit CRC in preclinical models. However, where the evidence is more limited, it is critical to transfer preclinical research into clinical data.